Fir and Spruce Mortality at Deoban - Khan, M. A. Waheed; Yadav, J. S. P.; Gupta, A. C. (Indian Forester, 1961)
Fir (Abies pindrow) and spruce (Picea morinda) forests at Deoban suffered abnormal mortality, following the heavy fellings done during 1941 to 1950. The cause of this mortality has been assessed from various angles and it has been concluded that as fir and spruce preferentially require a cool and moist habitat and though can withstand a tolerable amount of shade in early stages are still susceptible to permanent stagnation. Sudden exposure by way of inordinately heavy fellings of a long over-stocked forest may cause death of trees with indiscrimination. The physical and biological balances being upset, the adverse effects are all the more pronounced due to superficial, non-massive root systems of these species, and the abnormal reduction in crown length, either due to continued overcongestion or the deterioration set in by sudden excessive exposure. In the Indian forestry literature, this is the first record of mortality caused due to upsetting the physical and biological balances through heavy fellings.